ANALYSIS OF SERVICE QUALITY, TRUST IN CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE AT PT. BRI FINANCE - Subianto, Tri Bagus (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to test and analyze the quality of service, trust has a positive and significant effect on customer loyalty at PT. BRI Finance. Method: The population used in this study is 160 customers of PT. BRI Finance. This study uses primary-quantitative data collected through questionnaires and then processed with the SMART-PLS Version 24 application. The analysis technique used is SEM analysis. Results: The results of the study show that service quality has a positive and significant effect on customer satisfaction at PT. BRI Finance. Trust has a positive and significant effect on customer satisfaction at PT. BRI Finance. Customer satisfaction has a positive and significant effect on customer loyalty at PT. BRI Finance. Novelty: Customer satisfaction as an intervening variable in the relationship between service quality and trust has a positive and significant effect on customer loyalty at PT. BRI Finance.